Synthesis of Cyclohexane-Angularly-Fused Triquinanes - Jeon, Hongjun; Winkler, Jeffrey D. (Synthesis, 2020)
Cyclohexane-angularly-fused triquinanes, 6-5-5-5 tetracycles, have attracted the attention of synthetic chemists due to their highly congested core structures and multiple quaternary carbon centers. This review focuses on the six completed total synthesis of naturally occurring cyclohexane-angularly-fused triquinanes in addition to seven notable methodologies that have been developed for the synthesis of these structures.1 Introduction2 6-5-5-5 Tetracycles Containing a Linear Triquinane2.1 Total Synthesis of Cyclopiane Diterpenes2.2 Synthetic Approach toward Aberrarane Diterpenes2.3 Intermediates in the Total Synthesis of Magellanine-Type Alkaloids3 6-5-5-5 Tetracycles Containing an Angular Triquinane3.1 Total Synthesis of Waihoensene3.2 Miscellaneous Approaches4 Conclusion
Keywords: cyclohexane-angularly-fused triquinane; 6-5-5-5 tetracycles; natural products; total synthesis; cyclopianes; waihoensene